Human adaptation strategies to abrupt climate change in Puerto Rico ca. 3.5 ka. (April 2015) - Rivera-Collazo, Isabel; Winter, Amos; Scholz, Denis; Mangini, Augusto; Miller, Thomas; Kushnir, Yochanan; Black, David
The connection between climatic change and social response is complex because change articulates a number of inter-related factors. Human decisions are filtered by social buffers – including social memory, risk perception, and cultural priorities – and the rate and scale of climate change is usually much larger than the scale of human decision-making. In this article, we provide information on climate change based on precisely dated speleothems with the response evident in archaeological sites that have radiocarbon date ranges within the same time frame. A stalagmite recovered from within the catchment area for aquifer recharge of the Pre-Arawak site of Angostura in Barceloneta, Puerto Rico, shows that a significant wet period occurred between 3.9 and 3.1 ka (primarily centered at 3.5 ka). We investigate the effect that this increase in precipitation had on the earliest occupations on the island in the context of palaeoenvironmental, geoarchaeological, and archaeological records from Angostura, Maruca, and Paso del Indio. Our analysis suggests the presence of two different adaptation strategies: settlement relocation and microlandscape modification. Our study concludes that the social response to change cannot be seen as monolithic given that human behavior, even within the same period, addresses the needs of individual groups with different priorities. This multiplicity of responses can indeed enhance resilience as social support can continue through alliances and exchanges, strengthening social bonds that can help buffer catastrophes. The results can help shed light on the range of adaptation strategies to change encompassed within the manifestations of social resilience or vulnerability.